Customer Loyalty in Islamic Bank during the COVID-19 Outbreak: The Mediating Role of Trust and Satisfaction - Ahmad Syarif; Parno Parno; Kokom Komariah; Irma Yuliani (Journal of Economics, Business, and Accountancy Ventura, 2023)
Amidst the pandemic, Indonesia witnessed an economic downturn characterized by widespread layoffs, leading to an escalation in the unemployment rate and a decline in individual purchasing power. This crisis also bore down on the market share of Islamic banks. According to the 2021 survey conducted by the Islamic Financial Services Board (IFSB), the primary hurdles faced by Islamic banks during the pandemic were rooted in legacy infrastructure and technology. Loyalty, trust, and customer satisfaction are intricately linked to the quality of services provided, beginning with the customer's comprehension of Islamic banking. This study delves into the impact of knowledge on customer loyalty, with satisfaction and trust acting as mediating factors among Islamic bank customers in the context of the COVID-19 outbreak. Employing a quantitative approach, the study gathered data from 105 respondents based on the Isaac-Michael formula endorsed by the Islamic Economist Association in Yogyakarta in 2021, administered through questionnaires. The data was then analyzed using Structural Equation Modeling. The findings of this study underscore that knowledge significantly influences customer satisfaction, trust, and ultimately, loyalty. Additionally, satisfaction demonstrates a notable positive effect on loyalty. However, trust, in isolation, does not exert a direct influence on loyalty. Moreover, it was observed that knowledge directly impacts loyalty, and this effect is mediated by satisfaction, while trust does not serve as a mediator between knowledge and loyalty. In light of these findings, this study advocates for initiatives within Islamic banks to enhance financial literacy, provide accurate information, and foster understanding, countering any negative narratives that may erode public trust and perceptions. Furthermore, there is a pressing need to bolster digital services to ensure the continued loyalty of Islamic bank customers.